Identification and characterization of ferredoxin NADP+ reductase from Bacillus sp. - Othman, Sarah Syamimi (2015)
The aim of this experiment was to identify and characterize the enzyme ferredoxin NADP+ reductase from Bacillus sp. The gene was cloned and expressed in Escherichia coli system by using pEt102 TOPO vector as a host. The recombinant E. coli was cultured in Luria Bertani broth, and it was being induced with isopropyl-β-thioga-lactopyranoside (IPTG). Next, the expression culture was spun down by high speed centrifugation. Pellet was collected and resuspended with binding buffer and then sonicated. Centrifugation was repeated until the supernatant was collected and loaded on nickel-Sepharose chromatography. The purified ferredoxin NADP+ reductase was a protein with molecular mass of approximately 54kDa based on sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE). NADPH was a good electron donor meanwhile the electron acceptor was a 2,6-Dichlorophenolindophenol (DCPIP) in a diapharose assay. Furthermore, the maximum activity for this enzyme was observed at 25℃ and at pH 7. It had been proven that this enzyme could withstand for 120 minutes at 25℃ and at pH10. Results from experiment suggested that ferredoxin NADP+ reductase can be grouped as an oxidoreductase enzyme which had a capability to facilitate the reaction between NADP+/ NADPH with ferredoxin.